2021
DOI: 10.1002/path.5601
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 improves local immunity during Gram‐negative pneumonia by a combined effect on neutrophils and inflammatory monocytes

Abstract: Pneumonia represents a major health care burden and Gram‐negative bacteria provide an increasing therapeutic challenge at least in part through the emergence of multidrug‐resistant strains. IL‐33 is a multifunctional cytokine belonging to the IL‐1 family that can affect many different cell types. We sought here to determine the effect of recombinant IL‐33 on the host response during murine pneumonia caused by the common Gram‐negative pathogen Klebsiella pneumoniae. IL‐33 pretreatment prolonged survival for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Kp promotes inflammatory infiltration and cytokine storm, manifested by overproduction of IL‐1β, IL‐6, TNF‐α, IL‐13, IL‐33, and IFN‐γ 35–37 . Initially, we established the pneumonia mouse model via Kp infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kp promotes inflammatory infiltration and cytokine storm, manifested by overproduction of IL‐1β, IL‐6, TNF‐α, IL‐13, IL‐33, and IFN‐γ 35–37 . Initially, we established the pneumonia mouse model via Kp infection.…”
Section: Discussionmentioning
confidence: 99%
“…9,34 Moreover, SIRT1 acts as a crucial regulator of lung inflammation and macrophage polarization and modulates HMGB1 expression and acetylation. [35][36][37] HMGB1 inhibition plays a protecting role in Kp-infected mice and HMGB1 overexpression promotes proinflammatory polarization. 24,38 In the present study, we demonstrated that CA activates SIRT1 to inhibit HMGB1 acetylation and nuclear-cytoplasm translocation, thereby promoting M2 polarization and alleviating Kp-induced pneumonia (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia was induced in female C57BL/6 mice (Charles River, Maastricht, the Netherlands; 8–10 weeks of age) by intranasal inoculation of K. pneumoniae serotype 2 (43816; ATCC, Rockville, MD; 10 4 colony‐forming units, CFU) as previously described [ 11 13 ]. Bacterial counts were determined in organ homogenates and blood as described [ 11 13 ].…”
mentioning
confidence: 99%
“…Pneumonia was induced in female C57BL/6 mice (Charles River, Maastricht, the Netherlands; 8–10 weeks of age) by intranasal inoculation of K. pneumoniae serotype 2 (43816; ATCC, Rockville, MD; 10 4 colony‐forming units, CFU) as previously described [ 11 13 ]. Bacterial counts were determined in organ homogenates and blood as described [ 11 13 ]. Tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, IL-10, C-X-C motif ligand (CXCL)2 and myeloperoxidase (MPO) were measured in lung homogenates by ELISA according to manufacturer’s instructions (R&D Systems, Minneapolis, MN, USA).…”
mentioning
confidence: 99%
“…ST2 deficiency improves the outcome of Staphylococcus aureus -induced septic arthritis using the intraarticular infection model [ 34 ]; in a systemic infection model induced by a lethal intravenous dose of S. aureus , IL-33 administration protects against lethality via ILC2-dependent type 2 cytokine production [ 35 ]; in post-influenza S. aureus pneumonia, IL-33 diminishes bacterial loads and mortality by an effect that does not require ILC2 cells [ 36 ]. Furthermore, IL-33 increases bacterial loads and lethality through induction of type 2 cytokines in Legionella pneumophila -induced pneumonia [ 37 ], while IL-33 improves local immunity during Klebsiella pneumoniae -induced pneumonia by a combined effect on neutrophils and inflammatory monocytes but not on B, T, NK and ILC2 cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%